α-amylase inactivation during rice starch hydrolysis - Apar, DK; Özbek, B (ELSEVIER SCI LTD, 2005)
The effects of operating conditions on the enzymatic hydrolysis of rice starch were investigated using a commercial alpha-amylase produced by Bacillus spp. in a stirred batch reactor. The degree of starch hydrolysis (%) and residual a-amylase activity (%) were investigated versus process variables including pH, temperature, viscosity, impeller speed, processing time and some materials added such as hydrolysate, maltose, glucose. ethanol and CaCl2 using a stirred batch reactor. Mathematical models depending on the operating conditions were also derived using the experimental data of residual starch concentration. Some models were tested for understanding of the relationship between the process variables and enzyme stability during the hydrolysis process. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: rice starch hydrolysis; alpha-amylase inactivation; process variables; mathematical modeling; stirred batch bioreactor; WHEAT-STARCH; CHYMOTRYPSIN; MIXTURES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering